Interception performance of intake structures with a flow diversion barrier under supercritical flow conditions - Lu Chang (Engineering Applications of Computational Fluid Mechanics)
Intake structures are commonly used in drainage systems to redirect surface rainfall runoff into underground tunnels. The Hong Kong West Drainage Tunnel (HKWDT) system is designed to capture stormwater from steep upland catchments during periods of heavy rainfall, concurrently maintaining a minimal environmental flow downstream during dry weather. However, during heavy rainfall events, excess rainfall water is often directed into the drainage system, presenting a significant challenge to the urban drainage system. Undistorted Froude scale physical models and computational fluid dynamics (CFD) models are developed to investigate the flow performance. In this study, effects of various design parameters on water diversion performance are examined across a wide range of inflow conditions. Steeper channel bottom slopes leading to a larger proportion of water being directed downstream. Extending the length of the bottom rack effectively reduces adhering flow. Introducing a transverse barrier generates a hydraulic jump, which increases flow diversion into the LFC. With higher barrier heights, the hydraulic jump becomes stronger, facilitating greater water diversion into the downstream sewage system. The results indicate potential solutions to these challenges and provide valuable insights into optimizing flow diversion performance in intake structures, particularly in areas characterized by steep terrains and varying flow conditions.